2015
DOI: 10.1097/mib.0000000000000502
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Inflammatory Bowel Disease Among Patients with Autism Spectrum Disorders

Abstract: Across each population with different kinds of ascertainment, there was a consistent and statistically significant increased prevalance of IBD in patients with ASD than their respective controls and nationally reported rates for pediatric IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 27 publications
0
42
0
Order By: Relevance
“…Some studies found an association between gastrointestinal symptoms and severity of ASD symptoms (Adams et al, 2011;Wang L. W. et al, 2011;Mazurek et al, 2013), but others could not reproduce these findings (Kang et al, 2013;Son et al, 2015). ASD patients appear to have a higher prevalence of IBD (Doshi-Velez et al, 2015) and a higher number of pro-inflammatory immune cells in the intestinal wall (Navarro et al, 2016), although intestinal inflammatory markers, such as fecal calprotectin, appear normal (Navarro et al, 2016). The gastrointestinal symptoms may be caused by the presence of more pro-inflammatory gut bacteria (Fattorusso et al, 2019), but other factors may also be involved (Mayer et al, 2014).…”
Section: Neurological Disorders With Fmt Studies In Both Patients Andmentioning
confidence: 99%
“…Some studies found an association between gastrointestinal symptoms and severity of ASD symptoms (Adams et al, 2011;Wang L. W. et al, 2011;Mazurek et al, 2013), but others could not reproduce these findings (Kang et al, 2013;Son et al, 2015). ASD patients appear to have a higher prevalence of IBD (Doshi-Velez et al, 2015) and a higher number of pro-inflammatory immune cells in the intestinal wall (Navarro et al, 2016), although intestinal inflammatory markers, such as fecal calprotectin, appear normal (Navarro et al, 2016). The gastrointestinal symptoms may be caused by the presence of more pro-inflammatory gut bacteria (Fattorusso et al, 2019), but other factors may also be involved (Mayer et al, 2014).…”
Section: Neurological Disorders With Fmt Studies In Both Patients Andmentioning
confidence: 99%
“…31 Clinically, gastrointestinal complaints and increased incidence of inflammatory bowel disease (IBD) have been commonly reported with autism spectrum disorder (ASD). 32,33 One study comparing the intestinal microbiome of ASD patients to controls demonstrated alterations specifically in Clostridia and Bacteroidetes , Desulfovibrio classes. 34 Further study revealed increased levels of propionic acid (PPA), a short chain fatty acid fermentation product of Clostridia and Bacteroidetes, Desulfovibrio .…”
Section: Microbiota-gut-brain Axismentioning
confidence: 99%
“…However, a majority of children with ASD also suffer from a wide range of systemic aberrations such as increased serum serotonin (40% prevalence) [13], gastrointestinal (GI) distress (up to 90%) [4], and inflammatory bowel disease (IBD) [5]. Unfortunately, the causative agent for those conditions and their relationship with etiology and pathogenesis of ASD remains undefined.…”
Section: Introductionmentioning
confidence: 99%